Effects of fish meal replacement with composite proteins source on growth performance, antioxidant capacity and swim bladder quality of chu’s croaker (Nibea coibor) - Chunsheng Liu; Xin Liu; Jiarong Cai; Yuping Wang; Shuqi Wang; Xiaobo Wen; Hua Rong; Lanfei Xiao; Fan Lin (Aquaculture Reports)
Collagen, as a commercial functional protein, is widely applied in food, cosmetics, biomedicine and other industries, and swim bladder is regarded as an ideal source of raw materials due to its rich collagen content. Chu’s croaker (Nibea coibor), as an economical fish that can produce high-grade swim bladder, is popularly farmed, however, its high fishmeal demand limits the development of the feed industry. Therefore, it is worth thinking about how to reduce the use of fish meal without affecting the swim bladder quality. Given that, an 8-week feeding trial was conducted to investigate the effects of fish meal partially replaced (0.0%, 5.0%, 10.0%, 15.0%, 20.0%) with composite proteins (CPs, consisted of corn protein meal and hydrolyzed feather meal) on growth, antioxidant capacity and swim bladder quality (texture and collagen deposition) of chu’s croaker. Results showed that although growth performance decrease with the increase of CPs’ replacement level, it did not compromise the swim bladder quality. Specifically, 5% - 10% CPs did not affect the growth significantly, but can improve antioxidant capacity, protein content, collagen synthesis and texture quality of swim bladder. The enhancement of swim bladder texture, including hardness, chewiness, springiness, and adhesiveness may be caused by changes in the expression of related genes, such as colga1t1, col12a1, cyp27a1, etc. These results indicated that appropriate fish meal replaced by CPs could be applied during aquaculture practice after comprehensive consideration of feed cost, growth rate and quality of swim bladder. This study provides support for the development of cost-effective feed formulations that improve the sustainability and economic viability of chu’s croaker culture.